Consumers' perspectives on the use of EZ-link card for retail payments - Cao, Grace Shu Yin (2008)
This research paper outlines the study on consumers’ perspectives towards the use of ez-link card for retail payments in Singapore. It identifies the attributes consumers have and examines how these attributes differ between two groups of consumers - the users and non-users. The consumers’ perception has an impact on their adoption on the use and the marketing tactics needed to improve the likelihood of their adoption.